2010
DOI: 10.1007/s00246-010-9724-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lactate Levels Differ Significantly Between Surviving and Nonsurviving Patients Within the Same Risk-Adjusted Classification for Congenital Heart Surgery (RACHS-1) Group After Pediatric Cardiac Surgery

Abstract: This study aimed to examine the association between lactate levels in the first hours after surgery for congenital heart defects and the results of Risk-Adjusted Classification for Congenital Heart Surgery (RACHS-1) scoring and to evaluate serial lactate levels over time to determine whether they can serve as a supplementary tool for postoperative assessment within the same RACHS-1 group of patients. A retrospective cohort study was performed using data retrieved from a clinical database of 255 children who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
1
17
0
3
Order By: Relevance
“…However, the design of these studies was different, as the cut-off lactate levels were calculated as 3-6 mmol/L. [8,[12][13][14] Molina Hazan et al [8] found that maximum lactate levels (within postoperative first 12 hours) were correlated with the duration of CPB, duration of aortic cross-clamp, the RACHS-1 subgroups, and inotropic scores. Maarslet et al [12] reported that young age, low weight, high RACHS-1 scores, prolonged duration of CPB, and inotropic use were risk factors for elevated lactate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the design of these studies was different, as the cut-off lactate levels were calculated as 3-6 mmol/L. [8,[12][13][14] Molina Hazan et al [8] found that maximum lactate levels (within postoperative first 12 hours) were correlated with the duration of CPB, duration of aortic cross-clamp, the RACHS-1 subgroups, and inotropic scores. Maarslet et al [12] reported that young age, low weight, high RACHS-1 scores, prolonged duration of CPB, and inotropic use were risk factors for elevated lactate.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]8,[17][18][19] Cheifetz et al [3] reported that six of 48 patients who underwent high risk open-heart surgery died. The patients in the group in which the patients died had significantly higher lactate levels in the postoperative period than that of survivors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations